Frequency of Adverse Events of Antithyroid Drugs Administered during Pregnancy. (9th January 2014) - Yoshihara, Ai; Noh, Jaeduk Yoshimura; Watanabe, Natsuko; Iwaku, Kenji; Kobayashi, Sakiko; Suzuki, Miho; Ohye, Hidemi; Matsumoto, Masako; Kunii, Yo; Mukasa, Koji; Sugino, Kiminori; Ito, Koichi
Abstract : The frequency and types of adverse events after initial antithyroid drug (ATD) therapy during pregnancy have never been reported, nor has whether the frequency of adverse events is the same as among nonpregnant subjects ever been investigated. We investigated retrospectively the frequency of adverse events after initial ATD administration to previously untreated Graves' disease (GD) patients during pregnancy. We reviewed the charts of cases of 91 untreated pregnant women who came to our hospital for the first time and were newly diagnosed with GD during the period between January 1, 1999, and December 31, 2011. Thiamazole (MMI) was used to treat 40 patients and 51 patients were treated with propylthiouracil (PTU). Adverse events occurred in 5 patients (5/40; 12.5%) treated with MMI, and they consisted of cutaneous reactions in 5 patients. Adverse events occurred in five patients (5/51; 9.8%) treated with PTU, and they consisted of hepatotoxicity in two patients and cutaneous reactions in three patients. No patients experienced agranulocytosis or ANCA-related vasculitis. Comparison with the expected rate of adverse events in nonpregnant individuals showed that the frequency of adverse events in pregnant individuals was low.